Emotions and HIV/AIDS in South Africa: A multilingual perspective - Oostendorp, Marcelyn; Bylund, Emanuel (Stellenbosch Papers in Linguistics Plus, 2013)
This paper argues that in order to gain a more informed perspective on emotions and HIV/AIDS, crosslinguistic differences in emotion language need to be taken into account, particularly in a multilingual context. The paper reviews four published academic articles with the aim of illustrating how more consideration of the crosslinguistic and multilingual aspects of emotion language could have contributed to better theoretical understanding of HIV/AIDS and emotions as well as aiding the development of practical interventions in HIV/AIDS counselling and care. Finally, this paper argues that a lack of engagement with language and multilingualism around HIV/AIDS and emotions will stifle the development of a theoretical account of emotions as multi-semiotic and embodied, as well as the development of locally based, community-driven practical interventions.